Laser metal deposition of NiTi shape memory alloy on Ti sheet metal: Influence of preheating on dissimilar build-up - Scheitler, Christian Josef; Hentschel, Oliver; Krebs, Thomas; Nagulin, Konstantin Yu.; Schmidt, Michael (Journal of Laser Applications, 2017)
Lightweight and functional integration are two major drivers for additive manufacturing technologies. In order to integrate functionality, the use of smart materials like Nickel-Titanium (NiTi) shape memory alloys (SMAs) is a constructive approach. Generally, shape memory alloys are hard to machine and at the same time expensive materials. In this context, additive manufacturing processes like laser metal deposition are reasonable technologies to process these materials as the used powder can be recycled and near net shape geometry can be generated due to a layer-by-layer build-up process. For actuator applications, it might be reasonable to use hybrid systems, meaning just certain sections of a part are made of a shape memory material. One possible example is a NiTi shape memory element on a Ti sheet metal. Due to the varying coefficients of thermal expansion, a dissimilar build-up by means of laser metal deposition without any defects like cracks is challenging. In this paper, an approach that applies preheating is presented to generate SMA elements additively on dissimilar substrates by means of laser metal deposition. Subject of investigations are varying process parameter combinations (e.g., laser power, feed rate, and powder mass flow) and varying preheating temperatures. Based on metallographic analyses, the generated samples are evaluated. Major objective of these analyses are a defect free connection. Additionally, the forming microstructure and the occurring dilution zone are analyzed. In order to characterize the influence of different preheating strategies on the hardness and on the transformations temperatures of the generated parts, the results of hardness measurements and differential scanning calorimetry measurements are presented.
CRIS-Team Scopus Importer:2022-06-05